In Vitro Effects of Chlorhexidine and Isopropyl Alcohol Conditioning Agents on Immediate and Late Bond Strength of Fiber Posts to Dentin - Mansoureh Emami Arjomand; Negin Nasoohi; Mohaddeseh Shabani (Tehran University of Medical Sciences, 2024)
Objectives: This study assessed the effect of chlorhexidine (CHX) and isopropyl alcohol (IA) on immediate and late pushout bond strength (PBS) of fiber posts to dentin. Materials and Methods: In this in vitro study, 54 single-canal premolars were endodontically treated, and randomly assigned to 3 groups (N=18) for root dentin conditioning with distilled water (control), 2% CHX, and 70% IA after post space preparation. Fiber posts were cemented with TheraCem self-adhesive cement, and each group was subdivided into two subgroups (N=9) for PBS measurement immediately after bonding, and after  5000 thermal cycles (5-55°C). The roots were then sectioned, and their PBS was measured. The mode of failure was evaluated under a stereomicroscope at ×40 magnification. Data were analyzed by repeated measures ANOVA and Tukey's test (alpha=0.05). Results: The highest PBS was noted in the IA group (21.12 MPa) after 24 hours and the lowest PBS belonged to the control group after thermocycling (7.48 MPa). The immediate and post-thermocycling PBS were significantly lower in the control group than the CHX group (P<0.05). The PBS in both the control and CHX groups was lower than that in the IA group (P<0.001).  Regardless of the type of detergent, a significant reduction in PBS was observed after thermocycling (P<0.003). The PBS significantly decreased from the cervical towards the apical region in all groups (P<0.001). Conclusion: According to the results, application of IA before the self-adhesive cement effectively improved the immediate and late PBS, and was significantly more effective than CHX.